(untitled) (Journal of the College of Education for Women, 2019)
This study takes its importance in the area of systemic and historicalstudies because it stands on presenting such aspects from the systematicrespect and now Ibn AL-Jouzy dealt with the text of this subject and how hewas exact in telling them.Therefore, this study sheds light on the important aspects of thismethod in his book through reading and studying such texts whether they haddirect or indirect relationship with this subject.This study is not an easy task since it is based on contriving theintellectual aspects in the methods of lbn AL-Jouzy and how he deals with thetext of this subject in its hygienic, natural and geographical aspects inconstructing a historical method in most scripts, the general and the specific.